Photochromism: Photochromic Mechanism and Dual‐Phase Formation in Oxygen‐Containing Rare‐Earth Hydride Thin Films (Advanced Optical Materials 19/2020). Issue 19 (5th October 2020) - Hans, Marcus; Tran, Tuan T.; Aðalsteinsson, Sigurbjörn M.; Moldarev, Dmitrii; Moro, Marcos V.; Wolff, Max; Primetzhofer, Daniel
Abstract : Oxygen‐containing rare‐earth metal hydride thin films exhibit photo‐darkening upon light exposure; and in article number 2000822, the mechanism of the photochromic effect is unravelled by Marcus Hans and co‐workers. By combining X‐ray diffraction, transmission electron microscopy, and atom probe tomography, it is demonstrated that oxide and hydride phases are formed with significant compressive residual state. The reversible change in transparency can be understood as photon‐induced hydrogen transfer between two phases, identical in nature to the photochromic effect in bulk yttrium hydride at high pressure. [Artwork by CLS, RWTH Aachen University.]